2010
DOI: 10.1007/s12209-010-1390-6
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism and size prediction of bubble in opposite-flowing T-shaped microchannel

Abstract: Abstract:Bubble formation in an opposite-flowing T-shaped microchannel with 40 μm in depth and 120 μm in width was real-time visualized and investigated experimentally by means of a high speed camera. N 2 bubbles were generated in glycerol-water mixtures with different concentrations of surfactant sodium dodecyl sulfate (SDS). And the images were captured by the high speed camera linked to a computer. Results indicated that the bubble formation process can be distinguished into three consecutive stages, i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…When the liquid capillary number is less than 0.01, the bubble formation process conforms to the squeezing mechanism. Studies have shown a linear relationship between L B,0 / w and Q G / Q L under this condition as below: L normalB , 0 w = α + β Q normalG Q normalL where L B,0 is the initial bubble length (m) and w is the width of the microchannel (m).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the liquid capillary number is less than 0.01, the bubble formation process conforms to the squeezing mechanism. Studies have shown a linear relationship between L B,0 / w and Q G / Q L under this condition as below: L normalB , 0 w = α + β Q normalG Q normalL where L B,0 is the initial bubble length (m) and w is the width of the microchannel (m).…”
Section: Resultsmentioning
confidence: 99%
“…When the liquid capillary number is less than 0.01, the bubble formation process conforms to the squeezing mechanism. Studies have shown a linear relationship between L B,0 /w and Q G /Q L under this condition as below: 42 L…”
Section: Evolution Of Bubble Length and Liquid Filmmentioning
confidence: 92%